Cultural Intersections in Later Chinese Buddhism. Edited by Marsha Weidner. - Keyworth, George A. (Buddhist Studies Review, 2003)
Cultural Intersections in Later Chinese Buddhism. Edited by Marsha Weidner. University of Hawai'i Press, Honolulu 2001. ix, 234 pp. US$44.00. ISBN 0-8248-2308-7.